VD_FINDINFO HC / 2018 / 564 vom 15. Juni 2018 - VD Tribunal cantonal (2018)
DOLVICE DU CONSENTEMENT, FORFAIT, NOUVEAU MOYEN DE FAIT, NOVA, ÉTAT DE FAIT | 28 al. 1 CO, 373 CO, 310 CPC (CH), 311 al. 1 CPC (CH), 317 al. 1 CPC (CH), 55 CPC (CH)